Metabolic Engineering of the Chloroplast Genome Using the Echerichia coli ubiC Gene Reveals That Chorismate Is a Readily Abundant Plant Precursor for p-Hydroxybenzoic Acid Biosynthesis - Viitanen, Paul V. (American Society of Plant Biologists, 2004)
p-Hydroxybenzoic acid (pHBA) is the major monomer in liquid crystal polymers. In this study, the Escherichia coli ubiC gene that codes for chorismate pyruvate-lyase (CPL) was integrated into the tobacco (Nicotiana tabacum) chloroplast genome under the control of the light-regulated psbA 5′ untranslated region. CPL catalyzes the direct conversion of chorismate, an important branch point intermediate in the shikimate pathway that is exclusively synthesized in plastids, to pHBA and pyruvate. The leaf content of pHBA glucose conjugates in fully mature T(1) plants exposed to continuous light (total pooled material) varied between 13% and 18% dry weight, while the oldest leaves had levels as high as 26.5% dry weight. The latter value is 50-fold higher than the best value reported for nuclear-transformed tobacco plants expressing a chloroplast-targeted version of CPL. Despite the massive diversion of chorismate to pHBA, the plastid-transformed plants and control plants were indistinguishable. The highest CPL enzyme activity in pooled leaf material from adult T(1) plants was 50,783 pkat/mg of protein, which is equivalent to approximately 35% of the total soluble protein and approximately 250 times higher than the highest reported value for nuclear transformation. These experiments demonstrate that the current limitation for pHBA production in nuclear-transformed plants is CPL enzyme activity, and that the process becomes substrate-limited only when the enzyme is present at very high levels in the compartment of interest, such as the case with plastid transformation. Integration of CPL into the chloroplast genome provides a dramatic demonstration of the high-flux potential of the shikimate pathway for chorismate biosynthesis, and could prove to be a cost-effective route to pHBA. Moreover, exploiting this strategy to create an artificial metabolic sink for chorismate could provide new insight on regulation of the plant shikimate pathway and its complex interactions with downstream branches of secondary metabolism, which is currently poorly understood.